Assessing the phylogenetic dimension of Australian Acacia species introduced outside their native ranges. Issue 1 (2nd January 2016) - Yessoufou, Kowiyou; Mearns, Kevin; Elansary, Hosam O.; Hendrik Stoffberg, Gerrit
Abstract: Biological invasion is a long process that starts with humans introducing intentionally (most of the time) species into a new environment to benefit from the ecosystem services that these species provide. Increasing evidence suggests that species providing ecosystem services might be phylogenetically closer than expected, but only a few studies actually demonstrate this. Also, recent studies indicate that naturalized and invasive species are two functionally distinct groups, but evidence that they are also two phylogenetically distinct groups is mixed. Using the set of Australian Acacia species known to have been introduced intentionally by humans to several parts of the world for the ecosystem services they provide, we first tested whether there is a phylogenetic pattern in the subset of introduced species. We found that species moved beyond Australia are phylogenetically more closely related than expected at random, suggesting that the ecosystem services that guide human-mediated introduction of these species into new areas (e.g. famine food, medicines, fuel, fodder, ornament) may be shared between closely related species. We also found that naturalized non-invasive and naturalized invasive species are closely related and both are not a phylogenetically random subset of introduced species based on mean phylogenetic distance, suggesting that naturalization and invasion processes may be phylogenetically mediated. Collectively, our study indicates that phylogeny might play different roles at different stages of the biological invasion process.